Headache Currents Commentary. Issue 4 (4th April 2013) - Frishberg, Benjamin
<x xml:space="preserve">Abstract</x> Neuro‐ophthalmology is a field that interfaces intimately with headache medicine. Examples include common and uncommon visual disturbances related to migraine, painful loss of vision, eye pain, photophobia, pupillary disorders, and painful ophthalmoplegia. There are often articles relevant to headache specialists that are published in the ophthalmic literature. This commentary highlights 2 interesting clinical articles. All neurologists and headache medicine specialists should read the review on photophobia by Digre and Brennan as it is relevant, clinical, and comprehensive. The literature review on topiramate‐related acute angle‐closure glaucoma provides us with useful information about the epidemiology and pathophysiology of this rare but potentially vision‐threatening condition that may occur with the most widely used of migraine preventives.